A Database Tool for Raising Awareness on the Life Cycle Environmental Impacts of Household Packaging Waste. (3rd February 2014) - Abeliotis, Konstadinos; Zachos, Fotios; Lasaridi, Katia
Abstract : Packaging is a key stage of the life cycle of a product regarding its environmental impact. Also, the contribution of the households in the success of packaging recycling programs is well documented. The aim of this paper is the presentation of the development of a computer-aided tool that assists consumers in minimising their everyday environmental impact via the environmental assessment of the products' packaging coupled with the recycling behaviour of the consumer. The tool has been developed in Microsoft Access and consists of a user-friendly interface and four databases which contain data on the packaging materials of consumer products and their weights alongside with data for the recycling rates of various waste packaging materials in Greece. The user inputs the number of packages per product that he/she bought followed by his/her recycling habits. The tool then calculates the environmental impacts of his/her choices (both consumer and recycling). The key advantage of the developed computer tool is its simplicity, both conceptual and operable. On the other hand, its main drawback is that impact assessment data are based on Dutch conditions. Overall, the implications of the developed computer-aided tool for informing and raising consumer awareness on packaging waste recycling are enormous.